Rotational osteo-onychocutaneous flap for central polydactyly of the foot: A novel technique for correction of the deformity. Issue 8 (August 2022) - Hwang, Ji Sup; Kim, Jihyeung; Bae, Kee Jeong; Lee, Yohan; Baek, Goo Hyun
Abstract: Eccentric location of two nails like eyes of a bird are frequently observed in central polydactyly of the foot. A novel technique of rotational osteo-onychocutaneous (OOC) flap procedure is introduced to correct this deformity. Six children with central polydactyly of the foot who showed eccentric locations of nails were operated by this technique. Four patients were distal phalangeal type, and two middle phalangeal type. Preoperatively the angulation deformity of distal phalangeal type was average 16.8 (range, 2.3–48.0) degrees, and middle phalangeal type 10.3 (range, 2.9–17.7) degrees. The rotational OOC flap procedure was performed at average 24 (range, 12–51) months of age. Cosmetic and radiographic assessments were done after an average of 42 (range, 6–79) months of follow-up. All patients and their parents were satisfied with the cosmetic results. The angulation deformity was improved to average 4.2 (range, 0.5–11.2) degrees in distal phalangeal type, and 5.9 (range, 2.0–9.8) degrees in middle phalangeal type, respectively. Postoperative residual angulation deformity measured by simple radiographs were less than 5° in all patients. Complications such as partial necrosis of the flap were not found. In conclusion, our novel technique of rotational OOC flap procedure resulted in satisfactory outcome for patients with 'eyes of a bird' type toe nail deformity of central polydactyly of the foot. It corrected the angulation and rotational deformity of the toe nail of the main digit without causing any complications.